The Mexican Tourism Business: Lessons From Domestic Demand For Business Managers - Ruiz Fuentes, Liliana; Vargas Chanes, Delfino (Journal of Applied Business Research, 2018)
The purpose of this research is to identify priority actions to be taken in Mexico in order to encourage tourism entrepreneurs to take advantage of and to meet domestic tourist demand. In order to do this, the role that domestic tourism has in consumption and demand both nationally and internationally is analysed; opinion leaders from the sector are interviewed and the concept mapping methodology is used in combination with multidimensional scaling to solve the difficulties of prioritizing activities, gaining consensus, and to show graphically how the various stakeholders relate. The main results show three principal groups of activities: one which can be directly addressed by entrepreneurs, and two others, which although they relate to public policy and measurement, can also be driven by the business community.
Keywords: Concept Mapping; Domestic Tourism; Business Managers; Multidimensional Scaling